Economic evaluation alongside the Probiotics to Prevent Severe Pneumonia and Endotracheal Colonization Trial (E-PROSPECT): study protocol. Issue 6 (28th June 2020) - Lau, Vincent Issac; Cook, Deborah J; Fowler, Robert; Rochwerg, Bram; Johnstone, Jennie; Lauzier, François; Marshall, John C; Basmaji, John; Heels-Ansdell, Diane; Thabane, Lehana; Xie, Feng
Abstract : Introduction: Ventilator-associated pneumonia (VAP) is a common healthcare-associated infection in the intensive care unit (ICU). Probiotics are defined as live microorganisms that may confer health benefits when ingested. Prior randomised trials suggest that probiotics may prevent infections such as VAP and Clostridioides difficile –associated diarrhoea (CDAD). PROSPECT (Probiotics to Prevent Severe Pneumonia and Endotracheal Colonization Trial) is a multicentre, double-blinded, randomised controlled trial comparing the efficacy of the probiotic Lactobacillus rhamnosus GG with usual care versus usual care without probiotics in preventing VAP and other clinically important outcomes in critically ill patients admitted to the ICU. Methods and analysis: The objective of E-PROSPECT is to determine the incremental cost-effectiveness of L. rhamnosus GG plus usual care versus usual care without probiotics in critically ill patients. E-PROSPECT will be performed from the public healthcare payer's perspective over a time horizon from ICU admission to hospital discharge. We will determine probabilities of in-ICU and in-hospital events from all patients alongside PROSPECT. We will retrieve unit costs for each resource use item using jurisdiction-specific public databases, supplemented by individual site unit costs if such databases are unavailable. Direct costs will include medications, personnel costs, radiology/laboratory testing, operative/non-operative procedures and per-day hospital 'hoteling' costs not otherwise encompassed. The primary outcome is the incremental cost per VAP prevented between the two treatment groups. Other clinical events such as CDAD, antibiotic-associated diarrhoea and in-hospital mortality will be included as secondary outcomes. We will perform pre-specified subgroup analyses (medical/surgical/trauma; age; frailty status; antibiotic use; prevalent vs no prevalent pneumonia) and probabilistic sensitivity analyses for VAP, then generate confidence intervals using the non-parametric bootstrapping approach. Ethics and dissemination: Study approval for E-PROSPECT was granted by the Hamilton Integrated Research Ethics Board of McMaster University on 29 July 2019. Informed consent was obtained from the patient or substitute decision-maker in PROSPECT. The findings of this study will be published in peer-reviewed journals. Trial registration number: NCT01782755 ; Pre-results.